Pengaruh Budaya Dan Sertifikasi Halal Terhadap Loyalitas Konsumen Jamu Ramuan Madura Di Kecamatan Kwanyar - Qorirotul Uyun; Mashudi Mashudi; Dahruji Dahruji (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The demand for Madurese herbal medicine products is increasing significantly in every region, this cannot be separated from Madura herbal medicine producers as providers of halal products. In this study, the object of research was the producer of Madurese herbal medicine in the Kwanyar Madura sub-district area. This research was conducted on producers to find out what factors influence the influence of culture and halal certification on consumer loyalty. This research aims to find out the process of Madurese herbal medicine producers in Kwanyar sub-district to obtain halal certification from the halal product guarantee administration body (BPJPH) using an analytical approach. multiple linear variables through cultural influence, halal certification, consumer loyalty. The method used in this research is quantitative using multiple linear analysis tests. The sampling technique is the technique used for sampling in this research with a non-probability sampling technique using a purposive sampling approach. This test consists of normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, t test, f test, and multiple linear analysis.